Study on sanitary microbiological properties and genotoxic properties of Darhan City soil (Mongolian Journal of Agricultural Sciences, 2014)
The world population rising very fast and it has resulted in increasing the area of polluted soil, water and air. In order to cater to the demands of the people, the rapid expansion of industries, vehicles, etc. is necessary. But all of these developments make our world, especially urban area, heavily polluted. And many kind of contaminant substances showing bad effects to human health. Our research work aimed to evaluate Darhan city soil contamination using genetoxicological studies. Genotoxicological effect of soil contaminant substances or ability to cause a mutation to living organisms was determined by Eims test and DNA damaging experiment on test strain Salmonella thyphimurium TA-100 (his G46, rfa B, bio pKm 101) and Escherichia coli (wp, uvr, pol). The result revealed that Darhan city soil samples have inhibition effect to test strain growth rate. DOI: http://dx.doi.org/10.5564/mjas.v11i2.221 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.73-76